2004
DOI: 10.1111/j.1440-172x.2005.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential errors and their prevention in operating room teamwork as experienced by Finnish, British and American nurses

Abstract: This study describes how the potential sources of errors and error prevention in operating room (OR) teams are experienced by Finnish, American and British nurses. The data were collected by interviews and analysed using a qualitative content analysis. Results consisted of categories demanding teamwork practice, shared responsibility in teams and organized teamwork. The demanding practice category included fear of errors, turnover in teams, overtime work and emotional distress as potential factors leading to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 50 publications
(54 reference statements)
4
85
0
Order By: Relevance
“…This is significant since the utilization of expertise is important in the development of nursing [6,16,25,26] as the combined knowledge, skills of co-operating team members inevitably exceeds their individual knowledge and skills. In addition to processing information, the participants indicated that multiprofessional learning, responsibility and commitment were central to good teamwork, again in accordance with previous findings [8,11,12,19] .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This is significant since the utilization of expertise is important in the development of nursing [6,16,25,26] as the combined knowledge, skills of co-operating team members inevitably exceeds their individual knowledge and skills. In addition to processing information, the participants indicated that multiprofessional learning, responsibility and commitment were central to good teamwork, again in accordance with previous findings [8,11,12,19] .…”
Section: Resultssupporting
confidence: 78%
“…However, common goals, internal interaction, community spirit and shared expertise are also crucial elements of successful network co-operation and teamwork [10,11,17] . When assessing the functionality of teamwork, attention must also be paid to aspects such as: team structure; the roles of team members; whether the operational culture promotes co-operation, trust and a positive team atmosphere; feedback practices; conflict resolution; sharing of information; multiprofessional learning; personal relationships; responsibility; commitment; interaction skills; functional skills; and problem-solving [8,9,12,15,18,19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with a previous study (Cronqvist et al, 2001). Additional findings show that professional discussions and disagreements within an operating room team result in stress and could compromise patient safety (Silèn-Lipponen et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…In larger operating units, participants may not be so familiar with the other team members. Silén -Lipponen et al (38), found in their study that familiarity with team members and stability of teams, helped to combine the team members skills and fostered advanced planning, thus promoting safety. It is possible that surgical teams who are more familiar with each other, have a higher level of interdisciplinary cooperation and therefore may increase patient safety.…”
Section: Interaction Between Team Members In the Operating Theatrementioning
confidence: 99%